Generation and interpretation of images - Montesinos S.; Fernández L. (The use of remote sensing and geographic information systems for irrigation management in Southwest Europe, 2012)
A digital image is a representation of a real object using a numerical two-dimensional matrix where each element is called pixel. The digital process is the set of numerical transformations performed on the original matrix to obtain more appropriate representations of the image, depending on applications. Restoration processes are aimed to eliminate the radiometric errors sounds and geometric distortions generated during the compilation and transmission of data. The highlight consists on a set of techniques to improve the visual interpretation of the image. The multitemporal and multispectral character of remote sensing data allows transformations that produce new components or bands of the image.